Content Dissemination from Small-scale Museum and Archival Collections: Community Reusable Semantic Metadata Content Models for Digital Humanities - Avgoustinos Avgousti; Georgios Papaioannou; Feliz Ribeiro Gouveia (Code4Lib Journal, 2019)
This paper highlights the challenges in content dissemination in Cultural Heritage (CH) institutions by digital humanities scholars and small Museums and Archival Collections. It showcases a solution based on Community Reusable Semantic Metadata Content Models (RM’s) available for download from our community website. Installing the RM's will extend the functionality of the state of the art Content Management Framework (CMF) towards numismatic collections. Furthermore, it encapsulates metadata using the Resource Description Framework in Attributes (RDFa), and the Schema.org vocabulary. Establishing a community around RM’s will help the development, upgrading and sharing of RM's models and packages for the benefit of the Cultural Heritage community. A distributed model for Community Reusable Semantic Metadata Content Models will allow the community to grow and improve, serving the needs and enabling the infrastructure to scale for the next generation of humanities scholars.